The Effectiveness of Flipbook-Based E-Modules in Enhancing Conceptual Understanding in High School Physics Education - Putri Inda Sari; Qorry Listiyani; Salsabila (Yayasan Darussalam Bengkulu, 2023)
This study investigates the effectiveness of flipbook-based e-modules in improving high school students' conceptual understanding of physics. Flipbook-based e-modules integrate multimedia elements such as videos, animations, and interactive quizzes, offering a dynamic and engaging learning experience. A meta-analysis of 10 relevant studies was conducted to evaluate the impact of these e-modules on student engagement, academic performance, and conceptual understanding. The results show that flipbook-based e-modules significantly enhance students' understanding of complex physics concepts, with improvements in academic performance and increased student engagement. However, challenges related to technical issues and preparation time were also identified, suggesting the need for further development in the technical infrastructure and teacher training. This study contributes to the growing body of literature on multimedia learning tools, offering insights for educators seeking to incorporate interactive digital resources into their teaching practices.